(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
This paper explores how Trump-era American Muslim activists and organizations have contributed to the development of what we call an “Islamic Just Sustainability”. We explore how this emerging paradigm has restructured Muslim identity in the American context, while reinforcing a foundational shift in religious and sociocultural understanding of the environment and its corresponding intersectional identities. The paper will discuss how the Trumpian context has buttressed American Muslim activist networks that first arose in the post-9/11 environment then explore the development of Islamic Just Sustainability as a theological precept in the American Muslim community. Finally, we will explore the way American Muslim scholars and activists have promoted and implemented the Islamic Just Sustainability paradigm through the pulpit and in their communities.